Perlindungan Hukum Terhadap Pemilik Hak Atas Tanah Dalam Pemindahan Hak Atas Tanah Akibat Jual Beli Tanpa Izin (Studi Kasus Putusan Pengadilan Negeri Semarang No. 157/Pdt/G/2012/PN.SMG) - Amelia Ratna Febriyanti, Endang Sri Santi, Marjo (Diponegoro Law Journal, 2013)
In the civil case decided by Semarang District Court Number 157/Pdt/G/2012/PN.SMG, PT. Kekancan Mukti (Litigant) bought a land of 96,926 m2 by the name of Samsuri (Defendant I) who released his right on April 27, 1995. In March 2011, the Defendants brought in heavy equipments to the disputed object and did excavation activities and cut and fill. It was noticed that Defendant I had sold the land to Sutejo (Defendant II) with the proof of sell and purchase deed made by the Land Deed Officer of Tembalang Subdistrict.The research results show that the legal protection to PT. Kekancan Mukti is legal as the land owner because they have a strong evidence in the formof HGB certificate proving that the disputed land is their land in accordance with article 19 paragraph (1) of Agrarian Law (UUPA), that in order to ensure legal certainty by government held land registration and article 32 paragraph (1) of Government Regulation No. 24, 1997, certificate is a valid certificate as a proof of the strong evidence of the physical data and juridical data. PPAT Tembalang Subdistrict as the party who made the sell and purchase deed is not responsible for the dispute since PPAT Tembalang Subdistrict only performed his duty as PPAT and previously considered that Samsuri and Sutejo had a good will in accordance with article 1320 and article 1338 of Civil Code. Nevertheless, PPAT Tembalang Subdistrict did not perform his responsibility and function as PPAT because he did not check the deed signed to guarantee the authenticity of the data.